NAVIGATING THE COMPLETE PATIENT PATHWAY: ENSURING COHESION, COMMUNICATION, AND COLLABORATION AT EVERY STAGE OF THE HEALTHCARE EXPERIENCE - MOHAMMED ABDULLAH ALBEKAIRI, YASSIR ABDULLAH ALBEKAIRI, HANAA BAGHDAD ALMUTAIRI, ABEER KSABI AL ZAHRANI, JAWHARAH TURKI ALGHAMDI, MOHAMMD MANA ALASMARI, ATHEER MOHAMMED SALEH ALSUBAIE, NORAH OBAIDALLAH ALHARBI; NABEEL ALI ALTHABI, WALEED DHAIF ALLAH ALOTAIBI, SULTAN TALAQ SULTAN ALWITHYNANI, SALMAN TURKY ALTHEYABI, ABDULRAHMAN KHALID ABDULLAH ALAQEEL (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The contemporary healthcare landscape, marked by increasing specialization, often results in fragmented care that undermines patient experience and clinical outcomes. This study examines the concept of the integrated patient pathway as a critical framework for overcoming this fragmentation by ensuring cohesion, communication, and collaboration across the entire healthcare journey. It delineates the patient pathway from initial access and diagnosis through treatment, rehabilitation, and long-term management, highlighting the indispensable and interconnected roles of diverse clinical and administrative disciplines. The analysis identifies the core components of effective pathways, including clear governance, multidisciplinary involvement, robust information systems, and active patient engagement. It further explores the key enablers for successful implementation, such as strategic leadership, digital health technologies, and co-design methodologies that position patients as active partners. Conversely, the article addresses significant barriers, including organizational silos, communication gaps, and resource constraints, offering evidence-based strategies for mitigation.Ultimately, this study contends that a consciously designed, learning-system approach to patient pathways—one that standardizes best practices while allowing for local adaptation and continuous improvement—is fundamental to achieving seamless, high-quality, and sustainable patient-centered care. By synthesizing recent research and practical insights, it provides a comprehensive blueprint for healthcare organizations seeking to navigate the complexities of care delivery and enhance outcomes through strategic integration.